(untitled) (Journal of Hama University, 2024)
Calcium hydroxide intracanal medicament is used between treatment sessions to increase disinfection in root canals especially in necrotic cases. However, removing it from the root canal after performing its function is important because its remnants have negative effects on the bonding of the endodontic pastes to the root dentin, which negatively affects the apical seal and success rates of endodontic treatment. Aim of this research is to compare the efficacy of ethanol as an irrigant for removing calcium hydroxide intracanal medicament in comparison with different irrigants. This study was conducted on 38 single rooted mandibular premolars with mature apices, free from any internal or external absorption. The sample was divided into four main groups according to the irrigation solution used: (ethanol 70% - sodium hypochlorite 5.25% - EDTA 17% - saline). The sample was instrumented and injected with oil-based calcium hydroxide (Metapex Plus), then three-dimensional images were taken using cone-beam computed tomography (CBCT) before and after removal attempts to calculate the volume of the intracanal medicament remnants. One-way ANOVA was used to calculate differences between calcium hydroxide removal percentage, Bonferroni post hoc was used to compare the differences between the groups. Results showed no irrigation solution was able to completely remove calcium hydroxide medicament, but ethanol was more effective in removing the medicament from the root canal than sodium hypochlorite with statistically significant differences at 95% confidence level. We conclude that the use of ethanol is more effective than sodium hypochlorite solution in removing oil-based calcium hydroxide medicament.